Review of the NAFTA environmental side agreement: does it meet expectations? - Kelly, Mary E. (Frontera Norte, 2017)
Este artículo compara las posiciones originales que tomaron los gobiernos mexicano y estadounidense y las organizaciones ambientalistas con respecto a los acuerdos suplementarios al TLC, con el texto final de las negociaciones. El análisis se enfoca sobre trece puntos para demostrar dónde el acuerdo final se asemeja o diverge de las posturas originales. Los resultados sugieren que el proceso de negociación fue fuertemente influido por consideraciones políticas, y no por un deseo de crear instituciones transnacionales tripartitas. ABSTRACT This article conducts a side-by-side analysis of the initial positions of the Mexican and U.S. governments and environmental organizations on the environmental side agreement to NAFTA with the agreement text as it emerged from final negotiations. The analysis focuses on thirteen key issues to demonstrate where and how the final agreement accords or diverges from these positions, with the result seeming to suggest that the negotiation process was strongly influenced by NAFTA's political fortunes rather than a determination to establish a well-structured trinational institution.